Analisis Faktor-Faktor Yang Memengaruhi Muzaki Dalam Memilih Organisasi Pengelola Zakat (OPZ): Studi Kasus di Badan Amil Zakat Nasional Kota Bogor - Nadilla Ambarfauziah Rulian; Lukytawati Anggraeni; Deni Lubis (AL-MUZARA'AH, 2015)
The main purpose of management of zakat in Act No 23/2011 is to achieve public welfare and poverty alleviation. However, until now, zakat has not been sufficient to attain both these goals since zakat fund collected in Indonesia is only about 1% of its national potential that reaches Rp 217 trillion. This indicates that there are many muslims who are not motivated to pay zakat nor trust Zakat Management Organization. This study analyzes the factors that influence muzakki in choosing Zakat Management Organization and the performance of BAZNAS Kota Bogor from muzakki’s perception. Logistic regression is used to analyze the factors that affect muzakki in choosing the Zakat Management Organization. Descriptive analysis is used to analyze the perceptions of the BAZNAS Kota Bogor. This research was conducted during the month of February 2014 with 30 respondents BAZNAS Kota Bogor’s muzakki and 30 respondents muzakki whose paying zakat directly to mustahiq. The results of logistic regression show that the factors that affect muzakki in choosing Zakat Management Organization are income, the level of reliability, and institution’s image. The muzakki’s perception of the performance of BAZNAS Kota Bogor can be concluded as good, particulary in reliability, responsiveness, and tangible.